Towards the characterization of a novel thermohalophilic antioxidant Thioredoxin from the metagenome of the Red Sea; LCL of Atlantis II Brine pool - Abdelwahed, Mohamed Mohamed Gamal (AUC Knowledge Fountain, 2014)
Due to the crucial antioxidant role of Thioredoxin (Trx) system in various vital cellular processes; DNA synthesis, oxidative stress defense, protein folding, apoptosis and cell growth, this fundamental system is widely expressed in mostly all life's kingdoms. Thus using metagenomic approaches to characterize novel Trx system in unexplored harsh environment will open the window for understanding the evolution of Trx system and its unique adaptation in extreme habitations. One of the unexplored unique ecosystems is the Red Sea's Atalntis II brine pool, specifically, the lower convective layer (LCL). The exceptional harsh conditions of the LCL; anoxic condition, high temperature around 70°C, high salinity (26%), and high metal content, have a significant contribution for being a unique infrequent ecosystem. The objective of this study is to characterize a novel Trx isolated from the LCL. Successfully, in the experimental part, Trx was expressed in E. coli and purified, where the purified Trx has shown a clear antioxidant activity with a unique thermohalophilicity. In conclusion, we have characterized a unique antioxidant Trx protein.